Freedom, teleology, and evil - Goetz, Stewart (Continuum studies in philosophy of religion., 2008)
Stewart Goetz presents a thought-provoking defence of the existence of libertarian freedom of will, arguing that choices are essentially uncaused events with teleological explanations.